A novel, low surface charge density, anionically modified montmorillonite for polymer nanocomposites. Issue 10 (18th January 2017) - Yi, Deqi; Yang, Huixin; Zhao, Min; Huang, Le; Camino, Giovanni; Frache, Alberto; Yang, Rongjie
Abstract : A new, low surface charge density, anionically modified montmorillonite (MMT) has been prepared and its polyurethane nanocomposites are prepared. Abstract : A new, low surface charge density, anionically modified montmorillonite (MMT) has been prepared and its polyurethane nanocomposites are prepared. Their morphologies were studied using XRD, FTIR, SEM and EDS analysis, thermal stability by thermo-gravimetric analysis (TGA) and fire retardancy by cone calorimetry (CONE). Low surface charge density MMT forms due to conversion of [MgO6 ] − to [MgO5 OH] and [AlO4 ] − to [AlO3 OH] during the acidic treatment of MMT layers. Its anionic modification is related with p K a of modifier and pH of water solution by using Henderson–Hasselbalch equation. The low surface charge density MMT gives exfoliated nano-dispersion in PU, indicating that the dispersion of the MMT layers is not only decided by the organophilic surface, but also enhanced with a low surface charge density and electrostatic interaction between layers and counter ions. Low surface charge density MMT can enhance thermal stability and flame retardancy of PU with a small amount of anionic modifier, due to exfoliated nano-dispersion, and catalytic dehydrogenation and char formation. The large reduction in the THR for the sodium stearate modified low surface charge density MMT, SST-t-MMT, means that this material could be a solution for both fire risk and fire hazard.